PENGEMBANGAN BAHAN AJAR PENDIDIKAN LINGKUNGAN BERBASIS KEARIFAN LOKAL - Romi Kurniadi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2018)
This study aims to identify the concept and economic effects of local wisdom in environmental management. The results of the assessment will be developed as teaching materials on economic subjects. The method used is through the literature review related to the form of environmental management of Sungai Rangau watershed through local wisdom. The results of this study indicate that local wisdom-based environmental management has been conducted by Rantau Kopar communities living along the Rangau River flow in the planning, utilization, control and maintenance phase. Environmental management based on local wisdom is considered more economical compared to environmental exploitation which raises higher environmental normalization cost. Suistinable environmental maintenance will become the solution of scarcity problem, therefore the results of this study are appropriate to be applied as additional material in economic learning in high school in Basic Competence 3.1.2 on Analyzing economic problems and how to overcome them.